Air Force Enlisted Force Management System Interactions and Synchronization Strategies - Schiefer, Michael (RAND Corporation, 2007)
A fundamental goal of the Air Force personnel system is to ensure that the manpower inventory, by Air Force specialty code and grade, matches requirements. However, there are structural obstacles that impede achieving this goal. To remove one of those obstacles, the authors propose a methodology that would marginally modify grade authorizations within skill levels to make it possible to better achieve manpower targets.